The role of the International Organization for Migration (IOM) in upholding refugee rights in Indonesia based on the implementation of the 1951 refugee convention and the 1967 protocol - Azzaulfa, Anisa; Serera, Aulia Yuti (Priviet Social Sciences Journal, 2026)
Forced migration is a global issue that poses challenging legal challenges. Under Presidential Regulation No. 125 of 2016, Indonesia provides refugees with temporary protection, even though it has not joined the 1951 Refugee Convention or the 1967 Protocol. Even while the rule protects them, the legal framework restricts their ability to earn a living by prohibiting them from working, leaving them vulnerable and reliant on outside assistance. By contrasting its actions with the tenets of international refugee law, this paper investigates the role of the International Organization for Migration (IOM) in protecting refugee rights in Indonesia. The methodology is a normative-empirical legal approach that analyzes both the applicable legal instruments and the IOM’s factual practices based on official reports. The findings indicate that to bridge the gap created by the legal restriction on working, the IOM provides a monthly Cash-Based Intervention (CBI) allowance to support basic sustenance and align with the spirit of Article 23 of the Convention. Furthermore, the IOM covers tuition and supplies for refugees’ education, adhering to the standard set by Article 22 of the Convention. The IOM provides comprehensive insurance for healthcare, covering hospitalization, mental health, and reproductive health. These healthcare provisions fulfill the obligations outlined in Article 24. In conclusion, the IOM’s humanitarian interventions, specifically the provision of financial aid, education, and healthcare, are crucial in mitigating the acute vulnerabilities of refugees in Indonesia. These initiatives demonstrate a pragmatic dedication to maintaining social welfare norms and basic human rights in accordance with the 1951 Refugee Convention and the 1967 Protocol.